Performance Evaluation of Commercial Sunflower Threshers and their Role in Punjab - Maha, J S; Bal, A S; Manes, G S (Journal of Agricultural Engineering, 2003)
A survey of the sunflower growers and manufacturers in the state of Punjab was conducted to study the present status of sunflower thresher in the state. From survey of farmers it was established that decrease in area under sunflower crop after initial years of introduction was due to problems of threshing and marketing of the crop. However, with solution to the problems the area under cultivation of sunflower crop again increased. A simultaneous increase in threshers with area under sunflower is observed. Manufacturers modified and designed their own models further from original prototype developed at PAU Ludhiana in 1989. The major variation in design was found in case of threshing cylinder. In some machines blower was also not provided. All the performance indices, except cleaning efficiency, of the tested threshers were at par. Threshing efficiency in all the threshers was observed to be 100 per cent. Output in all the tested threshers was found to vary between 618 and 823 kg/h. Total losses were below 1.5 per cent in all the machines. The cleaning efficiency in case of thresher without blower was found about 5% lower than the thresher with blower.